Implementation of Halal Product Guarantee for Micro Enterprises - Muhammad Abduh (CIC Lembaga Riset dan Konsultan Sosial, 2021)
The implementation of Law Number 33 of 2014 concerning Halal Product Guarantee regulates the obligation of halal certification for business products. The obligation of dependent certification for micro business actors in harmonizing the program, it can be a challenge in itself considering the cost of certification is not cheap. The purpose of this study is to determine the implementation of halal product guarantees after the implementation of the Job Creation Law which changes some of the provisions of the Halal Product Guarantee as stipulated in Law Number 33 of 2014. This research is also conducted to find out in detail how micro-businesses are running in implementing halal product guarantees after the enactment of the Job Creation Law. Descriptive qualitative method is used in this study to adjust the opinion between the researchers and the information obtained. The choice of this method was made because the analysis could not be in the form of numbers and the researcher would rather describe all phenomena that exist in society clearly. This study found that the Job Creation Law was able to accommodate the problem of guaranteeing halal products for micro-entrepreneurs. Such as the problem of the severity of the cost of certification, the submission mechanism and the due date for issuing halal certification.